Prebiotically Plausible Organocatalysts Enabling a Selective Photoredox α‐Alkylation of Aldehydes on the Early Earth - Closs, Anna C. (Chemistry, 2020)
Organocatalysis is a powerful approach to extend and (enantio‐) selectively modify molecular structures. Adapting this concept to the Early Earth scenario offers a promising solution to explain their evolution into a complex homochiral world. Herein, we present a class of imidazolidine‐4‐thione organocatalysts, easily accessible from simple molecules available on an Early Earth under highly plausible prebiotic reaction conditions. These imidazolidine‐4‐thiones are readily formed from mixtures of aldehydes or ketones in presence of ammonia, cyanides and hydrogen sulfide in high selectivity and distinct preference for individual compounds of the resulting catalyst library. These organocatalysts enable the enantioselective α‐alkylation of aldehydes under prebiotic conditions and show activities that correlate with the selectivity of their formation. Furthermore, the crystallization of single catalysts as conglomerates opens the pathway for symmetry breaking.